Texts and Images in Aquaman Movie (A Multimodal Discourse Analysis) - Nur Afnita Asfar; Asrofil; Ni Wayan Kasni (International Journal of Systemic Functional Linguistics, 2022)
This study discussed texts and images in Aquaman Movie using a multimodal discourse analysis by Kress and Van Leeuwen's (2006) theory. The objectives of this study are to find out how the texts and images modes are used in the movie and how is the meaning of the text related to the meaning of the image. This research used the descriptive qualitative method. The source of data in this study was taken from Aquaman Movie. The data was collected through downloading, reading the dialogue, watching, screenshotting, selecting and coding the data based on the theory Kress and Van Leeuwen (2006). The result found the text and image components are used to know and identify the meaning contained in the Aquaman movie, which aims to provide information to readers and viewers through the modes displayed in the movie. The texts and images mode explain each other’s meaning and show related and non-conflicting meanings so that, can be easily understood by the public. Keywords: Aquaman Movie, Images, Multimodal Discourse Analysis, Texts